PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 7 TITI AKAR - Purba, Rosdiana; Antosa, Zariul; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted because of the low of science learning result of grade V students of SD Negeri 7 Titi Akar, Minimum Criteria of Completeness (KKM) set at school, that is 70. From 20 students, the Minimum Exhaustiveness Criterion (KKM) is only 9 students (45 %), while students who have not reached KKM there are 11 students (55%) with an average grade grade 67.25. to overcome these problems then the researchers apply cooperative learning model type Two Stay Two Stray (TSTS). The purpose of this study is to improve the learning outcomes of science students of grade V SD Negeri 7 Titi Akar with the application of cooperative learning model type Two Stay Two Stray (TSTS). The result of data analysis is known at the initial score of the student's average score is 67.25 increase in Cycle I to 72,00, and in Cycle II it increases again to 77,25. Improvement of classical completeness of student learning outcomes, at 45% initial scores increased in Cycle I to 80%, in Cycle II increased again to 85%. Overall there was an increase of 40%. Activity of teachers, on Cycle I the average percentage of teacher activity is 66.16% with Good category increased in Cycle II to 91.60% with Excellent category. Overall there was an increase of 25.44%. Student activity also increased, in Cycle I the average percentage of student activity was 62.50% with Good category increased in Cycle II to 91.60% with Excellent category. Overall increase in student activity by 29.10%. The increase in the percentage of teacher and student activity was also accompanied by the increase in the average score of the students' learning outcomes from the initial score of 67.25 to the end of Cycle II to 77.25. From the data of the research analyst, it can be concluded that the application of cooperative learning model type Two Stay Two Stray (TSTS) can improve the learning outcomes of science students of grade V SD Negeri 7 Titi Akar.Keywords: Co-operative type Two Stay Two Stray (TSTS), study result of science